An investigation into the role of attitudes towards mathematics as a motivation for choosing vocational-technical secondary education - Venter, Petrus Albertus (Rhodes University, Faculty of Education, Department of Education, 1986)
From Introduction: As headmaster of a technical high school it is my responsibility to admit standard six pupils to this school. Often the refrain from parents is heard: "My son is weak in mathematics but good with his hands." These parents desperately seek a secondary education for their non-academic children. To what extent has the vicious circle of low achievement - negative attitude - lower achievement - despair already been established in these pupils as far as mathematics is concerned? How does this low self-concept in mathematics ability serve as a factor in deciding upon which career to follow, which type of high school to attend? Parents and the public at large seem to be ill-informed about the subjects offered at technical high schools. The mathematical character of these schools is especially undervalued. People often seem to think that the mathematics at a technical high school is easier than at other high schools. Furthermore, people do not realize that mathematics forms the cornerstone of any technical field of study. Failure in mathematics will inevitably lead to low marks or failure in technical subjects. It seems that many pupils who have already developed a defeatist attitude towards mathematics, seek entry into this type of high school. If so, then why? This study aims to elucidate the mathematical cognitive demands made by mathematically related subjects in a technical high school. At the same time possible relationships will be investigated between choice of type of high school (technical vs non-technical) and : i) attitudes to mathematics; ii) achievement in mathematics; iii) general academic achievement; iv) attitude to school. Pupils at standard five level have already established their attitudes towards subjects. For this study standard five boys from East London English and Afrikaans-speaking primary schools were involved. The reason why girls were not considered was to eliminate the variables of sex-related behaviours. Also, girls do not report in any large numbers for technical education as yet. The results of this study should be of use to those advising standard five pupils on their choice of type of high school. If satisfactory relationships are found between affective-cognitive variables and choice of high school, future researchers may use this towards the construction of a required profile for prospective pupils of technical high schools. There are of course, many other factors in the issue. Variables like social status, parents' own experiences, vested interests of academic high schools and many more are not considered in this study. It is conceded that any in-depth study into attitudes towards mathematics or into choice of type of high school is a many-faceted problem, the scope of which lies beyond this thesis. Suffice to admit that attitudes are complex dispositions resulting from the interactions between a number of affective, cognitive and psychomotor variables.
Keywords: School children -- South Africa -- East London -- Attitudes; Technical education -- South Africa -- East London; Mathematical ability